2013
DOI: 10.1371/journal.pone.0077746
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-1 Tat Protein Induces the Activation of CD8+ T Cells and Affects In Vivo the Magnitude and Kinetics of Antiviral Responses

Abstract: T cells are functionally compromised during HIV infection despite their increased activation and proliferation. Although T cell hyperactivation is one of the best predictive markers for disease progression, its causes are poorly understood. Anti-tat natural immunity as well as anti-tat antibodies induced by Tat immunization protect from progression to AIDS and reverse signs of immune activation in HIV-infected patients suggesting a role of Tat in T cell dysfunctionality. The Tat protein of HIV-1 is known to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 85 publications
3
30
0
Order By: Relevance
“…We hypothesized that the inactivated Tat toxoid would improve the protection offered by rhFLSC by inducing antibodies that would neutralize extracellular Tat and reduce the T-cell hyperactivation and dysfunction that exacerbates viral expansion that is induced by native extracellular Tat (35). Combinations of envelope and inactivated mutants of Tat have been reported to protect against homologous SHIV infection in cynomolgus macaques (36,37). Notably, Tat toxoid physically associated with rhFLSC in solution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that the inactivated Tat toxoid would improve the protection offered by rhFLSC by inducing antibodies that would neutralize extracellular Tat and reduce the T-cell hyperactivation and dysfunction that exacerbates viral expansion that is induced by native extracellular Tat (35). Combinations of envelope and inactivated mutants of Tat have been reported to protect against homologous SHIV infection in cynomolgus macaques (36,37). Notably, Tat toxoid physically associated with rhFLSC in solution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been demonstrated that anti-Tat immunity is important for disease control and restoration of immune functions [25,26], suggesting that Tat may contribute to immune activation. In accordance with this hypothesis, we have recently shown in murine models that Tat favors the activation and the expansion of antigen-specific cytotoxic T lymphocytes (CTLs) and modulates antiviral responses causing dysfunctions similar to those observed in HIV-infected individuals [22,27].…”
Section: Introductionmentioning
confidence: 57%
“…These transcription factors are regulated by or regulate interferon (IFN)-g and interleukin (IL)-2 signaling [34][35][36]. As we have shown in murine models that Tat enhances T-cell receptor stimulation favoring IFN-g production [27], and several works describe that Tat increases IL-2 release in CD4 þ T cells [13,15], we sought to determine whether Tat may favor the activation of human CD8 þ T cells affecting the expression of these transcription factors. We demonstrate here for the first time that CD8 þ T cells activated in the presence of Tat enhance their effector functions and display an increased expression of those transcription factors important for T-cell programming.…”
Section: Introductionmentioning
confidence: 99%
“…Serum and mucosal samples were collected at day 42 and tested for the presence of anti-Tat antibodies. 30,31 Anti-Tat IgG were present in sera of all animals ( Fig.2A) with titers comparable among groups (Fig. 2B).…”
mentioning
confidence: 65%